If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -6b + 27 = 0 Reorder the terms: 27 + 3a + -6b = 0 Solving 27 + 3a + -6b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + 3a + -27 + -6b = 0 + -27 Reorder the terms: 27 + -27 + 3a + -6b = 0 + -27 Combine like terms: 27 + -27 = 0 0 + 3a + -6b = 0 + -27 3a + -6b = 0 + -27 Combine like terms: 0 + -27 = -27 3a + -6b = -27 Add '6b' to each side of the equation. 3a + -6b + 6b = -27 + 6b Combine like terms: -6b + 6b = 0 3a + 0 = -27 + 6b 3a = -27 + 6b Divide each side by '3'. a = -9 + 2b Simplifying a = -9 + 2b
| 9w-3w-6w+3w+w=16 | | 13/22=7/x | | -10-b=-5b-6b | | 8(3n+1)=7(9n+4)+2 | | 3a-6b+27=0 | | 10p-4p=18 | | y(3y+2)+(y+3y^2)= | | 0.2=0.05d | | 7v-5v= | | 3x-7+2x+4=77 | | p=(11-2x)i+14j | | 5(3n+2)=6(7n+4)+7 | | 8q-6q=10 | | 2/7×=4 | | 1/5=1/20d | | 7y+2(y-5)=4(y+2)-2 | | 1/3(9-12x) | | x^2+6xi-10=0 | | 6+5=-7 | | 2c(3^2)-8c/4^2-11 | | 3x+6+5x+4=90 | | 2x^2-3ax-2a^2=0 | | 66=5v-9 | | x^2+6ix-10=0 | | 12n^2-35=13n | | --2/3h=-22 | | (2c(3^2)-8c)/4^2-11 | | 4(5x-9)=20-30 | | 2u+13=53 | | x-2/3=1-x/2 | | 8x-2y=16y | | f(x)=-2x-15 |